Introduction: The Promise and Pitfalls of Social Problem Solving Through the Courts and Legal Advocacy - Annette Ruth Appell (Washington University Journal of Law & Policy, 2009)
The Articles in this volume, question the validity of these dispute resolution models the law employs to solve problems rather than adjudicate rights, particularly in the context of problem-solving courts such as family and juvenile courts, domestic violence courts, mental health courts, and criminal drug and gun courts, and even smoking courts. Each Article calls for assessment and accountability of these tribunals. That is to say the Articles call for proof, rather than stereotypes and anecdotes, that these courts actually can and do solve problems. The other two Articles provide original assessments of legal approaches to problem solving in the context of environmental justice, an area that often is more focused on group interests than individual rights.
Keywords: Access to justice; Sociological jurisprudence; Child abuse; Civil rights; Domestic violence; Environmental activists; Environmental engineering; Family; Lawyers; Problem solving; Social services; Social workers